2021
DOI: 10.3390/nu13093149
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Adherence to a Priori-Defined Dietary Patterns Is Associated with Decreased Nutrition Impact Symptom Burden in Head and Neck Cancer Survivors

Abstract: Dietary intake is understood to contribute to nutrition impact symptoms (NIS) in patients with head and neck squamous cell carcinoma (HNSCC). The purpose of this study was to evaluate the performance of four a priori-defined diet quality indices on the presence of NIS 1 year following diagnosis using data on 323 participants from the University of Michigan Head and Neck Specialized Program of Research Excellence (UM-SPORE). Pretreatment dietary intake was measured before treatment initiation using a food frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…15,16 Commonly referred to as ‘oral cancer’, oral squamous cell carcinoma (OSCC), is the most concerning HNC worldwide. 17 HNCs (tumours of the lips, oral cavity, tongue, oropharynx, hypopharynx, and larynx) are the 6 th 17 or 9 th 18,19 most common malignant neoplasm globally. In 2021 alone, cancers of the oral cavity, pharynx and oesophagus accounted for 3.9% of US total new cases.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Commonly referred to as ‘oral cancer’, oral squamous cell carcinoma (OSCC), is the most concerning HNC worldwide. 17 HNCs (tumours of the lips, oral cavity, tongue, oropharynx, hypopharynx, and larynx) are the 6 th 17 or 9 th 18,19 most common malignant neoplasm globally. In 2021 alone, cancers of the oral cavity, pharynx and oesophagus accounted for 3.9% of US total new cases.…”
Section: Introductionmentioning
confidence: 99%
“…Many a priori diet quality indices used in the nutritional epidemiology literature emphasize the consumption of fruits and vegetables, although there is otherwise significant nuance in their computation. In previous analyses, we demonstrated the utility of select a priori diet quality indices for predicting cancer-related outcomes, including survival and symptomatology, in a cohort of newly diagnosed HNSCC patients [ 16 , 17 ]. We also showed that dietary patterns derived using a posteriori methods, i.e., employing principal components analysis to empirically extract dietary patterns from observed food frequency questionnaire (FFQ) data, and serum micronutrient concentrations were associated with serum proinflammatory cytokine levels in newly diagnosed HNSCC survivors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis of these cohort data found that a posteriori dietary patterns measured at baseline, i.e., those extracted from data with multivariate statistical procedures, predicted survival in this cohort ( 23 ). The question of whether a priori diet quality indices, which measure adherence to a set of established dietary guidelines and are more generalizable to the study or general population, predict survival has never been broached in the context of the HNSCC population, although the relationship between a priori diet quality indices and the presence of NIS 1-year following diagnosis has previously been investigated in this cohort ( 30 ). Furthermore, the dynamic nature of dietary intake is rarely a focus of these analyses, and dietary variables are implemented into analytical models as static or baseline values only.…”
Section: Introductionmentioning
confidence: 99%